Determinan Kejadian Anemia pada siswi Di SMAN 1 Teluk Belengkong Kabupaten Indragiri Hilir pada tahun 2019: Determinan Kejadian Anemia pada siswi - Ikhtiyaruddin Ikhtiyaruddin; Agus Alamsyah; Mitra Mitra; Ary Setyaningsih (Jurnal Kesehatan Komunitas, 2020)
Anemia is a medical condition in which the number of red blood cells or hemoglobin is less than normalis <12 gram/100ml. Province of Riau is a region wiyh high anemia rates in Indonesia with prevalence exceed the threshold (36%). Based on the results of a survey conducted at SMAN 1 of TelukBelengkong Indragiri Hilir Regency was obtained from 10 female students and 7 people who were anemia. The purpose of this research was the knowing relationship between menstruration, phyisical activity, consumption fe tablet, breakfast, vegetable consumption, tea consumptionwith anemia in female students in the SMAN 1 of Teluk Belengkong Indragiri Hilir Regency year 2019. This research is quantitative analytic with research design a cross sectional. The study population amounted to 90 people with a sample of 90 people. Sampling technique is total sampling with chi square test. The result 60 % have anemia,P value < 0,05 show have relationship between menstruration P value = 0,003 (POR = 4,2), phyisical activity P value = 0,001 (POR = 4,8), breakfast P value = 0,001 (POR = 6,8) and tea consumption P value = 0,014 (POR = 3,2)with anemia in female students in the Sunior High School 1 of Teluk Belengkong. No have relationship between consumption fe tablet P value = 0,355 (POR = 1,7) and vegetable consumption P value = 0,093 (OR = 0,4) with anemia in female students in the Sunior High School 1 of Teluk Belengkong. the conclusion is that there is a significant relationship between menstruation, physical activity, breakfast, and tea consumption among female students to the incidence of anemia at SMAN 1 Teluk Belengkong. It is recommended that the school collaborate with the puskesmas in periodic anemia examinations and provide counseling about anemia and prevention efforts